Biochar restructures plant–soil–microbe relationships in a woody cropping system. Issue 6 (2nd November 2021) - Nash, Jake A.; Miesel, Jessica R.; Bonito, Gregory M.; Sakalidis, Monique L.; Ren, Han; Warnock, Daniel; Tiemann, Lisa K.
Abstract: Biochars are porous charcoal‐like materials that can enhance soil health and plant growth, but their use has not been adequately evaluated in woody cropping systems. To fill this knowledge gap, we investigated the effects of two slow pyrolysis pine biochars on plant performance, soil physicochemical properties, extracellular enzyme activities, and root‐associated fungal community composition in an experimental Christmas tree plantation over 3 yr. Both biochars stimulated the activities of five extracellular enzyme activities between 67 and 446%, but appeared to reduce N availability. Structural equation modelling identified increased soil moisture as a potential mechanism of biochar's effects on all measured enzyme activities, whereas increased dissolved organic C was a possible mechanism of biochar's effect on N and P targeting enzymes. This finding suggests that biochar‐induced increases to dissolved organic C have a specific effect on nutrient targeting enzymes. Biochar was found to negatively impact tree growth and survival, but impacts varied between tree species and biochar type. High‐throughput sequencing showed that biochar decreased the diversity of root‐associated fungal communities, with the ectendomycorrhizal species Wilcoxina mikolae becoming hyper‐dominant on balsam fir in response to one of the biochars. Changes to root‐associated fungal communities may have been partially responsible for negative effects on conifer performance. Although our study identified negative effects of biochar on plant performance and fungal diversity, we also found widespread changes to soil chemistry and microbial function that might be leveraged in systems with more acidic soils or different crops to increase plant performance. Core Ideas: Biochar application increased soil extracellular enzyme activities up to fivefold. Dissolved organic C and soil moisture were increased by biochar. Decreases to N availability suggest biochar induced N immobilization. Biochar led to less diverse root fungal communities and dominance by Wilcoxina . The growth and/or survival of two conifer trees was decreased by biochar.